Case of acute pulmonary embolism in post pneumonectomy-a rare clinical presentation and management - B. V., Manjunath; Sahoo, Bhabani; Thakre, Gaurav; Gudage, Nitin (International Journal of Research in Medical Sciences, 2017)
With a history of right pneumonectomy, pulmonary embolism affecting bilateral pulmonary artery is rare and needs to be meticulously managed to prevent pulmonary infarction of the normal lung with a clinical decision regarding thrombolysis. A 64 years male diabetic and hypertensive with a history of right pneumonectomy 10 years back, presented to ER with dyspnea and 2 episodes of syncope with right leg pain and swelling for 3 days. BP was 140/90mmHg and pulse rate of 100/min. SPO2 in room air was 95%. ECG suggested S1Q3T3 with sinus tachycardia. Echocardiogram revealed features of pulmonary embolism. Venous doppler of right leg showed DVT and CT Pulmonary angiogram was suggestive of pulmonary embolism. High-sensitive troponin I and NT-pro BNP were negative. Diagnosis of submassive pulmonary embolism was made. Protecting the normal lung from infarction was of paramount importance. There was no indication for thrombolysis. Treatment with LMWH was initiated and overlapped with the novel oral anticoagulant (NOAC) dabigatran. Symptomatically patient improved along with a reduction in pulmonary arterial hypertension and improved RV function. Post pneumonectomy of one lung, protecting the normal lung from infarction is utmost important in a setting of pulmonary embolism. It is a rare case scenario. Clinical decision regarding thrombolysis should be taken carefully. In this case thrombolysis was not indicated as per guidelines. LMWH, oral anticoagulation and broad-spectrum antibiotic to prevent secondary lung infection are the mainstay in the treatment of submassive pulmonary embolism where thrombolysis is not indicated.